2014
DOI: 10.1007/s10534-014-9788-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the ArsA ATPase that restore interaction with the ArsD metallochaperone

Abstract: The ArsA ATPase is the catalytic subunit of the ArsAB As(III) efflux pump. It receives trivalent As(III) from the intracellular metallochaperone ArsD. The interaction of ArsA and ArsD allows for resistance to As(III) at environmental concentrations. A quadruple mutant in the arsD gene encoding a K2A/K37A/K62A/K104A ArsD is unable to interact with ArsA. An error-prone mutagenesis approach was used to generate random mutations in the arsA gene that restored interaction with the quadruple arsD mutant in yeast two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The ArsA ATPase, the catalytic subunit of the ArsAB As(III) efflux pump, receives trivalent As(III) from the intracellular metallochaperone ArsD. The interaction of ArsA and ArsD allows for resistance to As(III) at environmental concentrations ( Vahter, 2002 ; Yang et al., 2011 ; Pillai et al., 2014 ). In this study, we also identified a putative transcriptional regulator in PA1-Petro only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ArsA ATPase, the catalytic subunit of the ArsAB As(III) efflux pump, receives trivalent As(III) from the intracellular metallochaperone ArsD. The interaction of ArsA and ArsD allows for resistance to As(III) at environmental concentrations ( Vahter, 2002 ; Yang et al., 2011 ; Pillai et al., 2014 ). In this study, we also identified a putative transcriptional regulator in PA1-Petro only.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some researchers argue that the use of tellurium compounds may negatively affect the immune defense, interfering with the recruitment of neutrophils against bacteria ( Nguyen et al., 2013 ). Now, Arsenic enters the environment from both geochemical and anthropogenic sources, representing a global health issue affecting millions of people worldwide through environmental and occupational exposure ( Pillai et al., 2014 ; Kuivenhoven and Mason, 2021 ). It is a naturally occurring metalloid element, also found in the air and food products ( Carlin et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The quenching of intrinsic protein fluorescence has been used to examine the binding specificity in proteins that bind to trivalent arsenicals, including ArsA ATPase, , ArsD As­(III)/Sb­(III) metallochaperone, and ArsM As­(III) S -adenosylmethionine methyltransferase . NemR has one tryptophan residue, Trp167 (Figure S5), which is responsible for the majority of its intrinsic fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular function of the protein is associated with the active transmembrane transporter of arsenite (Table S2 ). The product of the arsA gene is an arsenite-stimulated ATPase that, when associated with arsB, forms a complex that functions as an anion-translocating ATPase (Pillai et al 2014 ). Additionally, higher taxonomic abundances were observed during the wet season (Fig.…”
Section: Discussionmentioning
confidence: 99%